A Competency-Based Analysis of Human Resource Development among Educators at Salafiyah Islamic Boarding Schools - Hantoro, Ramandha Rudwi; Yamin, Martinis; Rosadi, Kemas Imron (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This study critically analyzes the implementation of competency-based human resource development (HRD) practices among educators (asatidzah) in Salafiyah Islamic boarding schools (pesantren) in Indonesia’s Riau Islands. Employing a qualitative case study design, data were obtained through interviews, participant observations, document analysis, and focus group discussions across three pesantren. The analysis reveals persistent gaps in pedagogical, social, personal, and professional competencies despite the educators’ strong foundation in religious knowledge. HRD initiatives are found to be fragmented, lacking systematic planning, evaluation mechanisms, and alignment with contemporary educational standards. These findings indicate an urgent need for structured, contextually relevant HRD strategies that are both sustainable and responsive to the dual imperatives of Islamic education and modern pedagogical demands. This study contributes to the discourse on educational capacity building in Islamic institutions and calls for future research using mixed-method or longitudinal approaches to examine the systemic effects of competency-based HRD interventions.